PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP NILAI PERUSAHAAN DENGAN PROFITABILITAS SEBAGAI VARIABEL INTERVENING (Studi Pada Perusahaan Perbankan Di Bursa Efek Indonesia) - G. A Sri Oktaryani; I Nyoman Nugraha Ardana P; Iwan Kusuma Negara; Siti Sofiyah; I Gede Mandra (Distribusi - Journal of Management and Business, 2017)
This research examines the effect of Good Corporate Governance (GCG) on firm value by using profitability as intervening variable.  Profitability is proxied by Return On Asset (ROA) and Return On Equity (ROE). This study used a quantitative approach and path analysis. The population consists of 35 firms that were listed in Banking sector of Indonesian Stock Exchange over period 2013 – 2015. There are 34 firms are choosen as samples which has published GCG composit index throughout observation years and has not done corporate action that could affect the stock price directly. The findings show that GCG has positive and significant direct effect on firm value. Furthermore, ROA has positive impact on firm value; meanwhile ROE has negative impact on firm value. The results also show that the better the implementation of GCG the higher the Return on Asset. Moreover, the indirect effect of GCG on firm value through profitability is not significant. Keywords: GCG, profitability, ROA, ROE, firm value.